Health promotion campaigns using social media: association rules mining and co-occurrence network analysis of Twitter hashtags - Atousa Ghahramani; Maria Prokofieva; Maximilian Pangratius de Courten (BMC Public Health)
Abstract Background Social media hashtags play a significant role in increasing the visibility of health information by making it easier for people to explore health-related content. Health promotion campaigns use campaign-specific hashtags to disseminate health-related messages, enabling individuals to access accurate and timely resources and updates. The study aims to discover patterns of connection between hashtags and identify the most influential hashtags used on Twitter in the American Heart Month campaigns. Method We collected a total of 73,288 tweets containing #AmericanHeartMonth between January 2019 and March 2023 and retrieved 18,143 original tweets, 42,930 retweets, 2,519 quotes, and 20,846 likes related to the past five campaigns. We adapted co-occurrence network analysis to explore the patterns of relationships between hashtags and association rules mining to assess the quality and strength of association between the co-occurred hashtags. Result While #AmericanHeartMonth, #OurHearts, and #HeartMonth play central roles in all hashtag co-occurrence networks, the results of association rules mining indicate a significant association of #OurHearts within the networks. The highest density of hashtags has been observed in the quoted tweets, introducing a new range of hashtags such as #GoRedForWomen, #WearRedDay, #HeartDisease, and #HeartHealth by Twitter users, indicating the positive correlation between co-occurring hashtags and users' engagement. The results of quality measurements of association rules (Lift > 1) indicate positive relationships between the co-occurred hashtags in the top 5 rules in all data subsets. Conclusion We employed co-occurrence network analysis and association rules mining as powerful techniques to identify influential hashtags that may have a central role in health-related discussions and drive engagement within the co-occurrence hashtag network. In conclusion, we recommend additional hashtag structures in conjunction with heart health-related topics to improve community building and the effectiveness of disseminating messages in future heart health promotion campaigns. The study contributes to knowledge and practice by offering a structured and data-driven approach and providing practical guidance for public health practitioners, professionals, and organisations to optimise content, targeting, and messaging to reach and engage a broader audience with health-related information.